Car mechanics in the lab: Investigating the behavior of real experts on experimental markets for credence goods - Adrian Beck; Rudolf Kerschbamer; Jianying Qiu; Matthias Sutter (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2013)
Credence goods, such as car repairs or medical services, are characterized by severe informational asymmetries between sellers and consumers, leading to fraud in the form of provision of insufficient service (undertreatment), provision of unnecessary service (overtreatment) and charging too much for a given service (overcharging). Recent experimental research involving a standard (student) subject pool has examined the influence of informational and market conditions on the type and level of fraud. We investigate whether professional car mechanics - as real sellers of credence goods - react in the same way to changes in informational and institutional constraints. While we find qualitatively similar effects in the fraud dimensions of undertreatment and overcharging for both subject pools, car mechanics are significantly more prone to supplying unnecessary services in all conditions, which could be a result of decision heuristics they learned in their professional training.
Keywords: C91; D82; C72; 330; artefactual field experiment; car mechanics; credence goods